Autoria em produções de pré-vestibulandos: uma análise de textos de alunos do projeto de extensão Entretextos do departamento de Letras (UFMA) - VILANOVA, Rosana de Carvalho (2022)
In the present research we made an analysis of the authorship processes in essays written by students of the Course of Textual Production, of the Entretexts Extension Project, of the Department of Letters of UFMA (DELER-UFMA). We aimed to analyze how students construct authorship in the context of a writing course "pre-vestibular", which is part of a university Extension Project. For such, we chose as methodology the qualitative field research and for the data treatment, we took into consideration the indicative paradigm proposed by Ginzburg (2007, p. 177). We analyzed four (04) texts, which were collected in September 2021, year in which we observed the classes of the Entretexts Project. The criterion for choosing the genre in question came from the observation that the students feel insecure when they know that when facing a textual type, such as the dissertative (the most demanded in college entrance exams), they must elaborate arguments and put themselves as authors of their text, to defend their opinion on the proposed theme. In this research we rely on the theories of French Discourse Analysis and Textual Linguistics, highlighting in these studies the authors: Foucault (1992, 1999, 2000), Possenti (2002; 2013) Orlandi (1988, 2007, 2020), Cavalcante (2018), Marcuschi (2008), among others. From the analyses of the Entretextos texts of students, we observed that text design, argumentation and coherence are inseparable and fundamental elements in the construction of authorship.